Pendekatan Komunikasi Interpersonal dalam Pembangunan berdasarkan Perspektif Kultural (Studi Kasus : Pro-Kontra Pengembangan Pariwisata Pulau Meti di Kabupaten Halmahera Utara) - Singgalen, Yerik Afrianto (School of Communication - Atma Jaya Catholic University of Indonesia, 2020)
This article aims to describe the interpersonal communication approach for development based on the perspective of the Hibualamo culture forthe people of Meti Village in the case of the pros and cons of tourism development on Meti Island in North Halmahera Regency. The researchmethod used is qualitative with a case study approach. Meanwhile, the data collection technique used in-depth interviews, observation anddocument study. The results of this study indicate that the existence of the Tourism Industry in this case Meti Cottage on Meti Island canincrease regional investment and maintain environmental sustainability, but it has not been able to provide economic and social benefits for localcommunities because of the pros and cons. Culturally, the interpersonal communication approach plays an important role in the level of publicacceptance of increasing investment in the tourism industry. However, the conflict between the manager of the tourist attraction and thecommunity related to empowerment and resource use has resulted in a disintegration of interests for sustainable tourism.